Dari Konflik ke Kolaborasi: Strategi Kepemimpinan Orang Tua dan Guru di PAUD - Rifda Nailah Sari; Faniysa Nur Salsabila; Nuning Apriliyani; Syifa Ariella Syahda; Aslamiah Aslamiah; Celia Cinantya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This Research aims to identify the role of of leadership in addressing and bridging differences of opinion between teachers and parents regarding the educational methods used. The goal is to create a harmonious collaboration to optimize children's development. The research method employed is library research, by collecting and analyzing various relevant literature sources to understand effective leadership strategies in building collaboration between families and schools. The findings indicate that effective leadership in early childhood education (ECE) settings must be able to accommodate diverse perspectives through open communication, collaborative activities, and the development of trust between schools and parents.